The Influence of Prevention Message Form on Post Covid-19 Self-Protection Motivation - Kamal Kamal; Afdaliza Afdaliza (Lembaga Penelitian, Publikasi dan Pengabdian kepada Masyarakat (LP3M) Institut Bisnis dan Komunikasi LSPR, 2023)
The Covid-19 based on presidential regulations regarding the status of the Corona Virus Disease 2019 (COVID-19) pandemic, in which the president stated that the status of Covid-19 had ended and the factual status of Corona Vints Disease 2019 (COVID-19) had turned into an endemic disease in Indonesia. For this reason, all sectors of people's lives are returning to adjust their operations, including the education sector, one of which is that universities have started to carry out face-to-face education. the Jakarta Institute of Communication and Business has implemented face-to-face learning, students from outside Jakarta have started coming to Jakarta to start lectures. for this reason, socialization is still needed regarding team health protocol procedures with various forms of messages. Appropriate message forms can increase motivation for self-protection during lectures. For this reason, this study wanted to know the types of messages and the effectiveness of the messages conveyed, so the researchers used quasi-experimental or quasi-experimental research methods using 3 types of messages, namely threatening messages, persuasion messages and related threatening messages. with a persuasive message. The first sample was taken using a purposive sampling method, namely sampling based on consideration of characteristics that are in accordance with the research objectives. Of the three experimental groups, the type of threat message associated with persuasive messages was more effective in increasing self-protective motivation.